Intrauterine adhesion after hysteroscopic myomectomy of submucous myomas. Issue 2 (20th November 2022) - Takasaki, Kazuki; Henmi, Hirofumi; Ikeda, Utako; Endo, Toshiaki; Azumaguchi, Atsushi; Nagasaka, Kazunori
Abstract: Purpose: To evaluate the frequency of intrauterine adhesion (IUA) after hysteroscopic myomectomy, and to analyze the association of IUA and the location of submucous myomas and the use of postoperative barrier (POB). Methods: Hysteroscopic myomectomy was performed in 217 patients with submucous myomas. The retrospective investigation was performed, and the cases were divided into three groups: cases with solitary submucous myoma (SSM; group 1), cases with apposing submucous myomas (ASMs; group 2) and cases with submucous myomas that were far from each other or not in apposition to one another (not apposing submucous myomas: NASMs; group 3). As POB, intrauterine device with oxidized regenerated cellulose and silicon sheet was inserted immediately after surgery. Results: IUA formation after hysteroscopic myomectomy was more frequent in group 2 than groups 1 and 3 (p = 0.03 and 0.01, respectively), despite the higher rates of POB use (p = 0.02). There was no significant difference in IUA formation in cases with POB between each group ( p = 0.06 and 0.21, respectively). But in cases without POB, group 2 showed higher rates of IUA formation than group 1 ( p = 0.04) and group 3 ( p = 0.03). Multivariable analysis for IUA formation demonstrated that ASMs were a risk factor of IUA (hazard ratio [HR] = 27.9, p < 0.01), and the use of POB was a prognostic factor for reduction of IUA formation (HR = 0.08, p < 0.01). Conclusion: ASMs appear to be a risk factor for IUA formation. The use of POB may be associated with preventing IUA formation after hysteroscopic myomectomy.